Intravitreal Injection of Conbercept Combined with Minimally Invasive Photocoagulation and Phacoemulsification Intraocular Lens Implantation in the Treatment of Neovascular Glaucoma Complicated with Cataract - Xue Li; Dawei Zhang (Journal of Ophthalmology)
Background. Neovascular glaucoma (NVG) is a complex refractory glaucoma with a high rate of blindness. Compaq is an anti-VEGF agent that has been used in clinical NVG therapy. Objective.This study aims to investigate the effect of intravitreal injection of conbercept combined with minimally invasive photocoagulation and phacoemulsification intraocular lens implantation in the treatment of NVG complicated with cataracts. Methods. A total of 84 patients with NVG complicated with cataracts who were admitted to our hospital from September 2019 to September 2021 were selected. According to the random number table method, they were divided into the study group and the control group, with 42 cases in each. The control group underwent minimally invasive photocoagulation combined with phacoemulsification and intraocular lens implantation. The study group was given an intravitreal injection of conbercept first, followed by minimally invasive photocoagulation combined with phacoemulsification and intraocular lens implantation 3 to 7 days after the injection. The intraocular pressure and visual acuity of the two groups before surgery, 1 week, 1 month, 3 months, and 6 months after the operation were compared. The levels of serum vascular endothelial growth factor (VEGF) and interleukin-6 (IL-6) were compared between the two groups before the operation and 1 week after the operation. The incidence of postoperative complications in the two groups was statistically compared. Results. At 1 week, 1 month, 3 months, and 6 months after the operation, the intraocular pressure of the study group was lower than that of the control group, and the visual acuity was better than that of the control group (P < 0.05); one week after the operation, the serum levels of VEGF and IL-6 in the study group were lower than those in the control group (P < 0.05); there was no significant difference in the incidence of complications between the two groups (P > 0.05). Conclusions. Intravitreal injection of conbercept combined with minimally invasive photocoagulation and phacoemulsification intraocular lens implantation in the treatment of NVG complicated with cataract can improve the levels of serum inflammatory factors and vasoactive substances, effectively reduce intraocular pressure, and improve visual acuity.